Yellow Fever Vaccination in a Mouse Model Is Associated With Uninterrupted Pregnancies and Viable Neonates Except When Administered at Implantation Period - Silva, Fernanda C. da; Magaldi, Fernanda M.; Sato, Helena K.; Bevilacqua, Estela (Frontiers in Microbiology, 2020)
The potential risk of yellow fever (YF) infection in unvaccinated pregnant women has aroused serious concerns. In this study, we evaluated the effect of the YF vaccine during gestation using a mouse model, analyzing placental structure, immunolocalization of the virus antigen, and viral activity at the maternal-fetal barrier and in the maternal liver and fetus. The YF vaccine (17DD) was administered subcutaneously at a dose of 2.0 log10 PFU to CD-1 mice on gestational days (gd) 0.5, 5.5, and 11.5 (n = 5–10/group). The control group received sterile saline (n = 5–10/group). Maternal liver, implantation sites with fetus, and placentas were collected on gd18.5. The numbers of implantation sites, reabsorbed embryos, and stillborn fetuses were counted, and placentas and live fetuses were weighed. Tissues (placenta, fetuses, and liver) of vaccinated pregnant mice on gd5.5 (n = 15) were paraffin-embedded in 10 % buffered-formalin and collected in TRIzol for immunolocalization of YF vaccine virus and PCR, respectively. PCR products were also subjected to automated sequence analysis. Fetal growth restriction (p < 0.0001) and a significant decrease in fetal viability (p < 0.0001) occurred only when the vaccine was administered on gd5.5. In stillbirths, the viral antigen was consistently immunolocalized at the maternal-fetal barrier and in fetal organs, suggesting a transplacental transfer. In stillbirths, RNA of the vaccine virus was also detected by reverse transcriptase-PCR indicating viral activity in the maternal liver and fetal tissues. In conclusion, the findings of this study in the mouse suggest that vaccination did not cause adverse outcomes with respect to fetal development except when administered during the early gestational stage, indicating the implantation period as a susceptible period in which the YF vaccine virus might interfere with pregnancy.